Human keratin matrix use and wound healing outcomes in post-acute care of pressure ulcers: Evidence from a Bayesian real-world study (International Journal of Tissue Repair, 2026)
Aims: To evaluate the real-world effectiveness of a human keratin matrix (HKM) compared with standard of care (SOC) in promoting pressure ulcer (PU) healing among patients treated in post-acute care settings.Methods: This observational comparative effectiveness study analyzed deidentified PU-level data from the LiftOff Registry, a national real-world database capturing post-acute wound care delivered in long-term acute care hospitals and skilled nursing facilities. PUs treated with HKM plus SOC were compared with those managed with SOC alone. Bayesian propensity score methods were used to reduce confounding and balance baseline demographic and clinical characteristics measured at PU identification. Healing—defined as complete epithelialization or closure—was modeled using Bayesian logistic regression with study arm and baseline PU stage as predictors. Treatment effects were summarized as posterior risk ratios (RR) with 95% highest density intervals (HDI) and posterior probabilities of benefit.Results: Before matching, the SOC cohort included 9356 patients with 14,740 PUs (33.2% healed), while the HKM cohort included 58 patients with 81 PUs (54.3% healed). After matching, 161 PUs were analyzed (81 HKM; 80 SOC); most were Stage 3 or Stage 4. HKM treatment was associated with higher modeled probabilities of healing compared with SOC alone. The posterior mean RR for healing was approximately 1.6 (95% HDI ≈ 1.0–2.1), with a posterior probability of benefit (RR > 1) of approximately 99.4%.Conclusion: In this real-world post-acute care cohort of patients with PUs, HKM use was associated with a high posterior probability of improved healing compared with SOC alone. These findings support HKM as an adjunctive therapy for complex or non-healing pressure ulcers in post-acute care settings.